Tracing the Footsteps of Ethnomathematics in Indonesian High School Education: Literature Metasynthesis and Trend Analysis 2015-2025 - Jatnika, Sugih Nugraha; Agoestanto, Arief; Mariani, Scolastika (Department of Mathematics Education Program IPI Garut, 2025)
Matematika sering dianggap sebagai pelajaran yang abstrak dan jauh dari kehidupan nyata. Padahal, konsep matematika banyak ditemukan dalam budaya lokal Indonesia. Penelitian ini bertujuan mengkaji penerapan etnomatematika dalam pembelajaran matematika di SMA melalui Tinjauan Literatur Sistematis (SLR) terhadap 20 artikel yang terbit antara 2015–2025. Artikel tersebut mencakup pengembangan bahan ajar, eksperimen kelas, serta integrasi unsur budaya seperti permainan tradisional, rumah adat, seni, dan tradisi lokal, terutama pada materi geometri, aljabar, dan bilangan. Hasil sintesis menunjukkan bahwa 85% studi melaporkan peningkatan pemahaman konsep, dan 70% menyebut peningkatan motivasi dan keterlibatan siswa. Etnomatematika juga memperkuat identitas budaya dan sikap positif siswa terhadap matematika. Pendekatan ini efektif menjembatani materi akademik dengan kehidupan nyata siswa. Kesimpulannya, etnomatematika layak diintegrasikan dalam kurikulum SMA untuk menciptakan pembelajaran yang kontekstual, bermakna, dan berakar pada budaya lokal. Mathematics is often considered an abstract subject, one that is far removed from real life. Mathematical concepts are widely found in local Indonesian culture. This study aims to examine the application of ethnomathematics in high school mathematics learning through a Systematic Literature Review (SLR) of 20 articles published between 2015 and 2025. The articles cover the development of teaching materials, classroom experiments, and the integration of cultural elements such as traditional games, traditional houses, art, and local traditions, especially in geometry, algebra, and number materials. The synthesis results showed that 85% of studies reported an increase in conceptual understanding, and 70% mentioned an increase in student motivation and engagement. Ethnomathematics also strengthens students’ cultural identity and positive attitudes towards mathematics. This approach effectively bridges academic material with students’ real lives. In conclusion, ethnomathematics is a valuable addition to the high school curriculum, as it fosters contextual, meaningful, and culturally rooted learning.